ENACTING AN ARTIFICIAL INTELLIGENCE-BASED LEARNING MEDIA TO SUPPORT VOCABULARY MASTERY AT SMA NEGERI 2 GEROKGAK: A MIXED METHODS STUDY - Antini, Ade Juni; Santosa, Made Hery; Kusuma, I Putu Indra (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
This study explores the impact of the Busuu application on students' vocabulary mastery and their perception of its implementation in eleventh-grade classes at SMA Negeri 2 Gerokgak. The research aims to address the lack of vocabulary teaching in Indonesia and the challenges faced by teachers in incorporating technology into vocabulary instruction. Educational technology, including the Busuu application, offers opportunities for students to learn independently and access a wide range of learning materials that are designed for learning foreign languages, providing users with feedback from native speakers and downloadable lessons. Previous studies have highlighted the positive impact of Busuu on students' motivation and vocabulary learning. This study utilizes a mixed methods research design, combining quantitative data analysis and qualitative interviews. The research is conducted over seven meetings with eleventh-grade students to improve their vocabulary skills. The study examines the statistical significance of increased vocabulary acquisition among Busuu users and analyzes qualitative data to gain insights into students' perceptions of the app. The findings of this research contribute to the improvement of language learning practices in Indonesia and provide valuable insights for language learners and educators. The study's significance lies in informing teachers about various learning media and their impact on English language teaching Furthermore, the research helps schools improve existing learning media and keep up with educational developments. However, the results indicate that Busuu is a valuable platform for vocabulary learning, creating a positive learning atmosphere. In conclusion, the study demonstrates the effectiveness of the Busuu application in improving students' vocabulary mastery. It highlights the importance of incorporating technology into vocabulary instruction and provides insights for further research in this field.